DETERMINANTS IN NATIONAL HEALTH INSURANCE SCHEME AWARENESS AND PARTICIPATION IN KADUNA STATE - Ekpo, Regina; Mamman, M.; Akpu, B. I.; Arigbede, Y. (FUDMA JOURNAL OF SCIENCES, 2024)
National Health Insurance Scheme (NHIS) is a social basic service offered by the Federal Government of Nigeria to its citizen, in order to achieve universal healthcare (UHC) coverage but its progress seems to be facilitated or hindered by some factors. This paper seeks to access the determinants of NHIS participation of Kaduna State. Adopt multiple stages sampling in the collection of data from 400 respondents. Frequencies, percentages and tables were used to present results obtained but applied Pearson product moment correlation coefficient to test for significant relationship at 0.01significant levels. The result shows that majority (80.1%) of NHIS participants in the study are within the productive and reproductive age group, married with children, have a minimum household size of five but enrolled 3-4 family members (28.8%), educated, 45% are income earners that obtain health services from mainly private HCFs with distance that is less than 5km, and awareness in NHIS had positive relationship with age, sex, number of children and household size. Positive relationship existed between age, household size, education, monthly income earned and immediate participation in NHIS while duration in NHIS participation had positive relationship with income and immediate participation in NHIS but employment status had a negative relationship. The paper recommends a comprehensive public awareness on NHIS participation that surpasses the office environment and encourages informal sectors to participate in NHIS is needful and avoids delay in participation after been informed about the scheme, for a successful UHC coverage.